SYNTHESIS AND MODIFICATION OF CHITOSAN FROM SHRIMP SHELL WASTES FOR ENHANCED OIL RECOVERY APPLICATION - (NIM : 20511048); Pembimbing :Prof. Dr. Ing. Cynthia L. Radiman, MUJIANTO
Enhanced oil recovery is a tertiary method used for improving oil production by fluid injection to a reservoir. Polymer for enhancing oil recovery should fulfill some requirements, such as resistant to temperature, high shear rate and high salinity. The objective of this research is to synthesize and to modify chitosan for enhanced oil recovery application. The chitosan was synthesized from chitin which was isolated from shrimp shell wastes through three stages, namely deproteinization, demineralization and deacetylation. The deacetylation degree of chitosan determined by the baseline method of IR spectra was 58.4 %. The molecular mass of chitosan determined by using an Ostwald viscometer was 1.49ÃƒÂ—106 g/mol. Then, the chitosan was modified by graft copolymerization of acrylamide using microwave-initiated grafting method. The grafting of chitosan was conducted by varying the mass of chitosan and the exposure time. The optimal reaction condition was reached when the reaction was carried out at 110 s exposure time, 2 M acrylamide and 0.1 g chitosan in 25 mL of formic acid. The results of FTIR measurement showed that the chitosan-graft-acrylamide was succesfully synthesized. The rheological properties of chitosan-graft-acrylamide (Chi-g-AM) was characterized using a Fann VG viscometer and the results were compared to a commercial polymer called HyboMax. The rheological measurements indicated that the Chi-g-AM solution viscosity decreased relatively similar to HyboMax solution by increasing temperature, but the viscosity of Chi-g-AM solution was more resistant to high shear rates. The resistant test toward salinity was carried out by adding salts, i.e. NaCl, KCl and CaCl2 to the polymer solution. The results showed that the Chi-g-AM solution had a higher resistance to salinity than the commercial product (HyboMax). However, in order to obtain high viscosity, higher concentration of Chi-g-AM is still needed.